Fenomena Sirang So Sirang Dalam Keluarga Masyarakat Batak Toba (Studi Kasus Kelurahan Kampung Baru Tanjungpinang Barat) - Naomi Prilda Siagian; Nanik Rahmawati; Rahma Syafitri (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study describes how the phenomenon of Sirang so sirang in the Batak Toba family with various factors experienced in the family. Marriage in Batak society is not limited to the decision of a pair of humans, but rather the decision of the indigenous community. Because one of the functions of marriage in Batak society is to uphold the Dalihan Natolu order. Separation relationship (Sirang so Sirang) or no longer related as husband and wife but not yet divorced. Sirang so sirang is considered to be an alternative path that has been chosen as a way out of family problems without divorce, because divorce is very rare and the consequences are very burdensome, not even permitted by the Toba Batak culture. Because the Batak people highly value marriage and race against religion so the divorce rate is very low. Batak culture wants marriage to be a marriage that remains one forever. This study used a qualitative descriptive method whereby the selection of research sampling used a purposive sampling technique and then analyzed the results of interviews based on field facts. Sources of data were obtained by in-depth interviews with 3 informants who experienced Sirang so sirang and additional informants from traditional leaders and church servants, while literature studies were obtained from books, journals and internet sources relevant to the object under study. After the data was analyzed, information was obtained that the factors causing Sirang so Sirang in Kampungbaru Tanjungpinang Barat Village were due to a third party, an affair committed by someone and domestic violence. These three things were each experienced by the 3 informants interviewed by the researchers. So that the consequences of Sirang so sirang are unclear status, imbalance in the family, and the separation of the two large families that have united them. Sirang so sirang cannot resolve family conflicts, so parents, traditional leaders, and church elders must take part in this problem explicitly so that Sirang so sirang is no longer an option when a family experiences conflict. This is because Sirang so sirang cannot resolve the family conflicts they experience, but only gives hope for reconciliation and also minimizes the fights that occur.